2017
DOI: 10.1104/pp.16.01743
|View full text |Cite|
|
Sign up to set email alerts
|

The IQD Family of Calmodulin-Binding Proteins Links Calcium Signaling to Microtubules, Membrane Subdomains, and the Nucleus

Abstract: ORCID IDs: 0000-0002-3493-4800 (K.B.); 0000-0002-7146-043X (B.M.).Calcium (Ca 2+ ) signaling and dynamic reorganization of the cytoskeleton are essential processes for the coordination and control of plant cell shape and cell growth. Calmodulin (CaM) and closely related calmodulin-like (CML) polypeptides are principal sensors of Ca 2+ signals. CaM/CMLs decode and relay information encrypted by the second messenger via differential interactions with a wide spectrum of targets to modulate their diverse biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
146
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(158 citation statements)
references
References 121 publications
6
146
0
Order By: Relevance
“…Moreover, hypocotyls of the dark‐grown p35S::OsIQD14:GFP seedlings were highly sensitive to Oryzalin (Figure e‐f), further supporting the role of OsIQD14 in controlling MT stability (Komaki et al , ; Nakamura et al , ). Further analysis of whether OsIQD14 overexpression could change the cell shape of Arabidopsis hypocotyl cells showed the much elongated hypocotyl cells of Arabidopsis lines expressing OsIQD14 (p35S::OsIQD14:GFP) compared to those of TUA6 marker line (p35S::GFP:TUA6, Figure S4c‐e), similar to AtIQD16 (Burstenbinder et al , ), and confirming the OsIQD14 effects on cell shape.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Moreover, hypocotyls of the dark‐grown p35S::OsIQD14:GFP seedlings were highly sensitive to Oryzalin (Figure e‐f), further supporting the role of OsIQD14 in controlling MT stability (Komaki et al , ; Nakamura et al , ). Further analysis of whether OsIQD14 overexpression could change the cell shape of Arabidopsis hypocotyl cells showed the much elongated hypocotyl cells of Arabidopsis lines expressing OsIQD14 (p35S::OsIQD14:GFP) compared to those of TUA6 marker line (p35S::GFP:TUA6, Figure S4c‐e), similar to AtIQD16 (Burstenbinder et al , ), and confirming the OsIQD14 effects on cell shape.…”
Section: Resultssupporting
confidence: 66%
“…IQD proteins contain a conserved, 67 amino acid domain and were first identified in Arabidopsis where it is represented by a 33‐member gene family (Abel et al , ). Evidence form Arabidopsis showed that IQDs play important roles in leaf shape determination and xylem secondary cell wall architecture (Burstenbinder et al , ; Liang et al , ; Sugiyama et al , ). Most of the IQD genes have distinct expression patterns, preferentially in embryo, stomata, meristematic cells and elongating tissues (Burstenbinder et al , ; Wendrich et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Betatubulins are basic cytoplasmic proteins that form together with alpha-tubulins the microtubules which are a major component of the cytoskeleton (26). The dynamic microtubule cytoskeleton network coordinates cellular transport, cell shape, cell division and cell growth (27,28). In dependency to the alkalinization, we observe an increased abundance of a number of tubulins (Table 3).…”
Section: Sucrose Catabolism May Fuel Cell Wall Matrix Polysaccharidesmentioning
confidence: 87%
“…IQD16 belongs to a novel class of calmodulinbinding proteins with potential roles in cellular calcium signaling (Abel et al, 2005;Abel et al, 2013). Most IQD family members localize to microtubules, and overexpression of IQD16 alters microtubule organization and induces cell elongation (Bürstenbinder et al, 2017a;Bürstenbinder et al, 2017b). As input, we used 10 images per genotype of cotyledons from 5-d-old seedlings (Fig.…”
Section: Phenotype Analysis Of Cell Shape Mutantsmentioning
confidence: 99%
“…Seeds of the ktn1-5 T-DNA line (SAIL_343_D12) were obtained from the Nottingham Arabidopsis Stock Centre (NASC). Transgenic Pro-35S:IQD16 lines were generated by Agrobacterium tumefaciens-mediated transformation using the floral-dip method (Clough and Bent, 1998), as described in Bürstenbinder et al (2017b). Arabidopsis seeds were surface-sterilized with chlorine gas, and after 2 d of stratification at 4°C grown vertically on square plates containing Arabidopsis salt (ATS) medium and 0.5% (w/v) agar (Lincoln et al, 1990) at 20°C with cycles of 16 h light and 8 h dark.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%